Microwave-Assisted Extraction of Pectin from “Saba” Banana Peel Waste: Optimization, Characterization, and Rheology Study - Joel P. Rivadeneira; Tao Wu; Quincy Ybanez; Adeliza A. Dorado; Veronica P. Migo; Fidel Rey P. Nayve; Katherine Ann T. Castillo-Israel (International Journal of Food Science)
One way to valorize “Saba” banana peel waste is to extract high-value compounds, such as pectin, and use it for food applications. In this study, the parameters for the microwave-assisted extraction of pectin were screened and optimized using Response Surface Methodology. The pectin was purified and then subjected to characterization. Results showed that the optimum extraction conditions were 195°C, 8% solid-liquid ratio, and pH 3 hydrochloric acid (HCl), with predicted and actual yields of 12.8% and 14.2%, respectively. The subsequent purification method increased the purity of pectin by 300%. The pectin was found to be low-methoxy in nature and had an average particle size of 300 nm. The pectin application in whey protein isolate resulted in a shear-thinning fluid, with an improved viscosity compared to a control. When applied to a commercial orange juice, the in vitro digestion study showed that the fluid’s viscosity was higher before and during the gastric and intestinal digestion at the low physiological shear rate.